การศึกษาผลกระทบของข้อมูลความโน้มถ่วงพิภพที่มีต่อการปรับแก้โครงข่ายระดับชั้นที่ 1 ในพื้นที่ประเทศไทย - ทวีชัย ชูเชิด (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
The Orthometric Height of Vertical Benchmarks in the 1st Order Leveling Network in Thailand is referred by the Mean Sea Level. Now, these vertical benchmarks are widely distributed over Thai region and have been used as references for various engineering applications. In Thailand especially the Royal Thai Survey Department (RTSD), a relative gravimetric survey has been carried out. The gravity data can be considered as the main factor in developing more precise orthometric heights. In each specific area, the gravity data is very much dependent on its terrain and this variation will inevitably affect a calculation of an orthometric height for each 1st order vertical benchmarks. This paper aims to present an effect of the gravity data on the determination of orthometric height of the 1st order vertical benchmarks. The study result shows that the difference between the height level of the 1st order leveling survey and the height level of the study on junction benchmark is maximally different in Bangkok and its perimeter areas, Northern part of Ko Lak and Southern part of Ko Lak which are 0.07 , 37.6 and 1.2 mm. respectively. The results of the study can be used as a future practice of the 1st order leveling survey for Thailand.